2017
DOI: 10.1165/rcmb.2016-0268oc
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Signaling Regulates Myofibroblast Function during Alveolar Septum Formation in Murine Postnatal Lung

Abstract: Sonic Hedgehog (Shh) signaling regulates mesenchymal proliferation and differentiation during embryonic lung development. In the adult lung, Shh signaling maintains mesenchymal quiescence and is dysregulated in diseases such as idiopathic pulmonary fibrosis and chronic obstructive pulmonary disease. Our previous data implicated a role for Shh in postnatal lung development. Here, we report a detailed analysis of Shh signaling during murine postnatal lung development. We show that Shh pathway expression and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 53 publications
5
57
0
Order By: Relevance
“…Previous data implicated a role of Hh in postnatal lung development; the interruption of Hh signaling at earlier time points leads to enlarged alveolar airspaces. In the adult lung, the Hh pathway maintains mesenchymal quiescence and is dysregulated in disease such as COPD (5). These results suggest that the Hh pathways underlie the initiation, maintenance, proliferation, and survival of CSE-transformed epithelial cells.…”
Section: Introductionmentioning
confidence: 86%
“…Previous data implicated a role of Hh in postnatal lung development; the interruption of Hh signaling at earlier time points leads to enlarged alveolar airspaces. In the adult lung, the Hh pathway maintains mesenchymal quiescence and is dysregulated in disease such as COPD (5). These results suggest that the Hh pathways underlie the initiation, maintenance, proliferation, and survival of CSE-transformed epithelial cells.…”
Section: Introductionmentioning
confidence: 86%
“…Until recently, SCMFs remained inaccessible to isolation and analysis. We, and others, have shown that SCMFs are a subclass of lung mesodermal cells that are targeted by hedgehog signaling, and thus can be tagged and isolated using Gli1-cre ERT2 , a high-fidelity hedgehog reporter (Ahn and Joyner, 2004;Li et al, 2015;Kugler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The process of alveologenesis mainly takes part in the period of P0-P14 in mice (approximately equivalent to the first 6 months after birth in humans). Afterwards, from P14 through P28, the maturation of the alveoli occurs [1]. Many different signaling ligands and receptors are involved in the process of alveolarization: absence of Platelet derived growth factor alpha (Pdgfα) leads to lack of Pdgf receptor α expressing cells, which potentially form a progenitor population for the α-smooth muscle actin-expressing alveolar myofibroblasts [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Many different signaling ligands and receptors are involved in the process of alveolarization: absence of Platelet derived growth factor alpha (Pdgfα) leads to lack of Pdgf receptor α expressing cells, which potentially form a progenitor population for the α-smooth muscle actin-expressing alveolar myofibroblasts [2][3][4]. Sonic hedgehog (Shh) signaling is also required for proper alveolar myofibroblast differentiation [1]. In addition, in a newborn murine hypoalveologenesis model, Perl et al showed that the re-alveolarization induced by application of retinoic acid is dependent on Fgf signaling [4].…”
Section: Introductionmentioning
confidence: 99%